Effect of pipe configurations on flame propagation of hydrocarbons–air and hydrogen–air mixtures in a constant volume - Emami, S.D.; Sulaiman, S.Z.; Kasmani, R.M.; Hamid, M.D.; Che Hassan, C.R. (Elsevier, 2016)
It is commonplace in industrial installations to have different piping arrangements for the efficient transport of substances/materials. However, the processing industry has raised some major concerns in terms of safety, due to the accidental gas explosions that have occurred frequently and caused serious damage. It is the aim of this study to comprehensively analyse the governing factors involved in flame propagation inside different pipe configurations. This research investigates confined pipe explosions using straight, 90-degree bending, and tee-junction pipes with different obstacle placements. Hydrogen-, ethylene-, propane- and natural gas–air mixtures, over a range of concentrations (equivalence ratio, Ф = 0.6–1.4) have been used. The results show that, while there is no significant difference in the maximum pressure and rate of pressure rise in both tee-pipe arrangements investigated, the bending pipe consistently produces the worst set of results in terms of maximum pressure and flame speed in gas explosions, involving the most reactive mixtures. In addition, the detailed records of pressure traces and blast waves show that the duration of flame acceleration, the flame direction and the initial ignition point depend on the tee junction placement along the pipe length, resulting to different overall profile of the flame acceleration mechanism.